2014
DOI: 10.1016/j.jfineco.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Fails-to-deliver, short selling, and market quality

Abstract: We investigate the collective net impact on market liquidity and pricing efficiency of equity trades that result in fails to deliver ("FTDs"). Given the nature of the US electronic trade settlement system for stocks, such "FTD trades" should originate almost exclusively from short sales, and we confirm this empirically on the basis of a natural experiment arising from a regulatory event. For a sample of 1,492 NYSE common stocks over a 42-month period from 2005 to 2008, we find that such trades lead to the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…In the first three columns we report the marginal effect estimates for the Probit model. Previous literature has shown that fails to deliver are associated to the premium to be paid to borrow the asset (see for example Evans, Geczy, Musto, andReed, 2009 andFotak, Raman, andYadav, 2014). Therefore, we introduce specialness as explanatory variable and, as expected, the probability of a failto-deliver increases with the specialness of the bond.…”
Section: Fails-to-delivermentioning
confidence: 83%
See 1 more Smart Citation
“…In the first three columns we report the marginal effect estimates for the Probit model. Previous literature has shown that fails to deliver are associated to the premium to be paid to borrow the asset (see for example Evans, Geczy, Musto, andReed, 2009 andFotak, Raman, andYadav, 2014). Therefore, we introduce specialness as explanatory variable and, as expected, the probability of a failto-deliver increases with the specialness of the bond.…”
Section: Fails-to-delivermentioning
confidence: 83%
“…In these circumstances, when short-sellers are unable to find the bond, or not willing to pay the high specialness premium they may also decide to fail on the delivery. Previous literature has investigated these effects mainly on the stock market (Evans, Geczy, Musto, andReed, 2009 andFotak, Raman, andYadav, 2014). Some evidence for the US Treasury market is provided in Fleming and Garbade (2005) and more recently in Fleming, Keane, Martin, and McMorrow (2014).…”
Section: Fails-to-delivermentioning
confidence: 99%
“…Although there are more standard state‐space models in the literature (see, e.g., Fotak, Raman, & Yadav, ), we build on Brogaard et al () and Hendershott and Menkveld () because their models closely align with market microstructure theory.…”
mentioning
confidence: 99%
“…Though, naked short selling was blamed by the SEC for artificially exacerbating price declines during the financial crisis of 2008, there is mixed evidence in the literature on price manipulation by naked short sellers. Fotak, Raman and Yadav () do not find any evidence that short trades that result in FTDs are causally related to the failure of financial firms in 2008. They also find that short trades that result in FTDs and short sales that result in timely delivery have the same beneficial effect on market liquidity and price efficiency.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 98%
“…In spite of existence of any clear evidence of market manipulation using naked short selling, the SEC implemented locate and close-out requirement for short selling to reduce FTDs. Fotak, Raman and Yadav (2014) report that almost all delivery failures originate exclusively as a result of short trades. In the presence of short-sale constraints, stocks become overpriced (Asquith, Pathak and Ritter, 2005;Chang, Cheng and Yu, 2007).…”
Section: Introductionmentioning
confidence: 99%